Synthesis and characterization of magnetic nanoparticles for biomedical applications - Arsalani, Soudabeh (2020)
Magnetic nanomaterials with specific size and shape distributions have attracted a large interest in recent years due to their promising properties for biomedical applications. This thesis presents the results of the synthesis and characterization of superparamagnetic iron oxide nanoparticles (SPIONs) for biomedical applications. The first group of SPIONs was prepared by a simple green co-precipitation method at a mild temperature and capping by natural rubber latex (NRL) extracted from Hevea brasiliensis. The results showed core size, size distribution, magnetization and blocking temperature of the magnetic nanoparticles (MNPs) could be controlled by the NRL concentration. Importantly, NRL-coated MNPs showed higher magnetization compared to the bare MNPs that can suggest NRL is an effective stabilizing agent to cover MNPs with enhancing magnetization for biomedical applications. The performance of the bare MNPs and NRL-coated MNPs were investigated by magnetic resonance imaging (MRI) system. MRI results showed R2 relaxation strongly depends on the NRL shell thickness of MNPs and it decreases by increasing the shell thickness of NRL. In addition, the relaxivity ratios (r2/r1) can be controlled by adjusting the concentration of NRL. Therefore, NRL coated MNPs can be considered as effective contrast agents for MRI applications. The second group of SPIONs with fluorescent and radioluminescent properties were synthesized by the thermal decomposition method, covered with oleic acid (OA) and modified by anthracene (AN) and polyvinyl alcohol (PVA) as fluorophore and the dispersion agent in aqueous solution, respectively. This multifunctional nanocomposite exhibited sharp blue emission bands upon exposure to UV and X-ray. Furthermore, the radioluminescence intensity of this nanocomposite showed a linear relation with the X-ray dose rate, that is highly desirable for biomedical applications. The last part of this thesis was devoted to narrow the size distribution of IONP (EMG 700, Ferrotec) coated with anionic surfactants that carried out using low gradient magnetic separation (LGMS) (<15 T/m) method, to improve their performance as magnetic particles imaging (MPI) tracers. Samples before and after LGMS with different concentrations of magnetite (Fe3O4) nanoparticles were imaged in a preclinical MPI scanner. The images of the samples after separation showed an improved MPI resolution. Furthermore, we show that the LGMS technique is capable of separating larger MNP entities from the suspension in a short period of time which allowed us to adjust the size distribution and magnetic properties of MNP via timecontrolled magnetic separation.